CDK13-Mediated Cell Cycle Disorder Promotes Tumorigenesis of High HMGA2 Expression Gastric Cancer - Wu, Zhouying; Wang, Min; Li, Feng; Wang, Feng; Jia, Jianchao; Feng, Zongqi; Huo, Xue; Yang, Jie; Jin, Wen; Sa, Rina; Gao, Wenming; Yu, Lan (Frontiers in Molecular Biosciences, 2021)
The inhibitor of CDK4/6 has been clinically used for treating certain types of cancer which characterized by G0/G1 acceleration induced by CDK4/6-RB1 pathway. On the other side, the cell cycle relating molecules are abnormal in over 50% of the patients with gastric cancer (GC), but the efficiency of inhibiting CDK4/6 doesn’t work well as it is expected. In our study, we found HMGA2 promotes GC through accelerating S-G2/M phase, instead of G0/G1. We also found CDK13 is the direct target gene of HMGA2. Importantly, we analyzed 200 pairs of GC and the adjacent tissue and proved the positive relation between HMGA2 and CDK13; moreover, high expression of both genes predicts a poorer prognosis than the expression of single gene does. We explored the effect of the novel CDK12/13 inhibiting agent, SR-4835, on the HMGA2-high-expressed GC, and found inhibition of both genes jointly could reach a satisfied result. Therefore, we suggest that inhibition of CDK13 and HMGA2 simultaneously could be an effective strategy for the HMGA2-high-expressed GC. To detect the expression of both genes simultaneously and individually could be benefit to predict prognosis for GC.